PEMANFAATAN LIMBAH KULIT BUAH NANAS (Ananas comosus (L) Merr.) SEBAGAI MINUMAN PENCERNAAN PROBIOTIK - Fadhli, Haiyul; Suhery, Wira Noviana; Agustini, Tiara Tri; Ningsih, Yozi Fiedya (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
Conventional fruit processing for food and beverage production often ignores the potential benefits of fruit peels, resulting in the presence of useless waste. Pineapple peel (Ananas comosus L. Merr) is one of the most underutilized by-products, even though it contains valuable compounds such as bromelain, flavonoids, tannins, oxalates, and phytates that have antibacterial and probiotic properties. The purpose of this community service is to provide education to increase the knowledge of the Kualu Nenas Village community about the utilization of pineapple peel waste as a prebiotic drink. The method used is counseling with colored brochure media and a demonstration of making probiotic drinks. The results obtained from 50 respondents were 48 (96%) respondents with low knowledge level, 1 (2%) respondent with sufficient knowledge level, and 1 (2%) respondent with high knowledge level. The bivariate test was carried out using the Wilcoxon method, where the test obtained the results of the p value = 0.000, which can be concluded that there is a difference or there is an effect of giving brochures on public knowledge because the p value <0.005.